Characterization of Bacillus subtilis sporulation and bacteriophage infection via FT-IR spectroscopy. Issue 3 (2009) - Mysliwiec Mysliwiec, Tami H. Tami H.; Tierno Tierno, Anthony F. Anthony F.; Aurentz Aurentz, David J. David J.
Abstract : A comparative analysis on cultures from wild-type and sporulation mutants of Bacillus subtilis infected with pseudotemperate spore-converting bacteriophages was performed to discern differences in the chemical functionality of the cellular population. Variations in the cell surface chemistry of B. subtilis cultures were analyzed using attenuated total reflectance (ATR) Fourier transform infrared (FT-IR) spectroscopy of dried sample films on optical plates. Comparison of wild-type and phage infected cultures revealed an increase in the amount of aliphatic ester in the infected populations. Spectral analysis of cultures from bacteriophage infected sporulation mutants, spo0K and spo0J revealed varying levels of ester linkages.